A Neuronal Transcriptome Response Involving Stress Pathways is Buffered by Neuronal microRNAs - Manakov, Sergei A.; Morton, Andrew; Enright, Anton J.; Grant, Seth G. (Frontiers in Neuroscience, 2012)
MicroRNAs (miRNAs) are involved in whole transcriptome reprogramming, for example, during development, cancer and stress. A number of experimental approaches, including transfection of miRNA mimics and inhibitors, were developed to study the targeting of mRNA transcripts by miRNAs. Many individual miRNAs lead to destabilization of hundreds of mRNA targets, however the significance of this broad inhibitory potential for the whole transcriptome is poorly understood. We found that a variety of treatments of primary neurons and the brain trigger a neuronal response in a large set of mRNAs encoding stress related pathways. These mRNAs are preferred targets for two neuronal miRNAs, miR-124 and miR-434-3p. Addition of mimics and inhibitors for miR-124 and miR-434-3p confirmed that a significant proportion of stress inducible transcripts are putative direct targets of these two miRNAs. We uncovered a direct connection between transcriptome changes induced by neuronal stresses and gene expression regulation by neuronal miRNAs. We suggest that through targeting hundreds of stress inducible transcripts, miRNAs act as stabilizers of transcriptome states. We propose that this stabilizing function is a mechanism for the recently reported constraint of synaptic plasticity by miRNAs. Our finding is also important for interpretation of popular transfection experiments, where we found miRNA targets to be induced inadvertently.